1985
DOI: 10.1172/jci112020
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of chronic tubulo-interstitial disease in rats. Interactions of dietary acid load, ammonia, and complement component C3.

Abstract: The human end-stage kidney and its experimental analogue, the remnant kidney in the rat, exhibit widespread tubulointerstitial disease. We investigated whether the pathogenesis of such tubulo-interstitial injury is dependent upon adaptive changes in tubular function and, in particular, in ammonia production when renal mass is reduced. Dietary acid load was reduced in 143nephrectomized rats by dietary supplementation with sodium bicarbonate (NaHCO3), while control rats, paired for serum creatinine after 14 neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
283
2
8

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(312 citation statements)
references
References 39 publications
(38 reference statements)
11
283
2
8
Order By: Relevance
“…Several other studies demonstrated a significant association of serum K + <4.0 mEq/L and mortality, but the index of inflammation and follow up on CKD progression were not evaluated in sufficient detail [41][42][43] . Collectively, consistent with prior studies in animal CKD models [44] and known information of hypokalemia being a stimulator for ammonium genesis, angiotensin II, inflammatory mediators, and oxidative stress [28,45] , even mild degrees of hypokalemia, 3.5-4.0 mEq/L (which may be considered "normal") in patients with CKD can induce inflammation and poor clinical outcomes.…”
Section: Hypokalemiasupporting
confidence: 82%
See 1 more Smart Citation
“…Several other studies demonstrated a significant association of serum K + <4.0 mEq/L and mortality, but the index of inflammation and follow up on CKD progression were not evaluated in sufficient detail [41][42][43] . Collectively, consistent with prior studies in animal CKD models [44] and known information of hypokalemia being a stimulator for ammonium genesis, angiotensin II, inflammatory mediators, and oxidative stress [28,45] , even mild degrees of hypokalemia, 3.5-4.0 mEq/L (which may be considered "normal") in patients with CKD can induce inflammation and poor clinical outcomes.…”
Section: Hypokalemiasupporting
confidence: 82%
“…NH 4 + is generated in the proximal tubules and secreted into the lumen via [21,28,29] and potentially promoting ongoing kidney damage. Indeed, metabolic acidosis in CKD is associated with more rapid CKD progression [30,31] and increased mortality [32] .…”
Section: Positive Acid Balancementioning
confidence: 99%
“…Crry is heavily expressed within the glomerular mesangium of mice, as well as at the basolateral surface of the renal tubules (26), both of which are areas of C3 deposition in ischemic ARF. At baseline there is C3 deposition around the renal tubules indicating that there is a low level activation in the interstitium despite these inhibitors (25). In rats, treatment with an Ab to Crry led to renal injury marked by tubulointerstitial damage and cast formation, demonstrating the necessity of complement inhibition to prevent spontaneous tubular injury (27).…”
Section: Discussionmentioning
confidence: 99%
“…4). This has been attributed to complement activation by ammonia, which can modify C3 to form a C3 convertase and activate complement (25). C3 was present along Bowman's capsule and in small quantities within the glomerular mesangium.…”
Section: C3 and C9 Depositionmentioning
confidence: 99%
“…Taken together, if complement activation is truly etiologic in renal IRI, this must be occurring through the alternative pathway. The site of activation could be on the apical surface of tubules [because this site lacks complement regulators (2)] or on the basolateral surface [a site that is clearly susceptible to spontaneous complement activation (17) as is illustrated by the finding of C3 deposits in this location in normal animals (22)]. …”
Section: Discussionmentioning
confidence: 99%